2012
DOI: 10.1186/1746-6148-8-85
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability and pharmacokinetics of oral meloxicam in llamas

Abstract: BackgroundSouth American camelids in the United States have rapidly developed into an important agricultural industry in need of veterinary services. Pain management is challenging in camelids because there are no drugs currently approved by the U.S. Food and Drug Administration for use in these species. Dosage regimens used for many therapeutic drugs have been extrapolated from other ruminants; however, the pharmacokinetics, in camelids, may differ from those of other species. Studies investigating the pharma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
40
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 37 publications
5
40
1
Order By: Relevance
“…Previous studies have demonstrated excellent bioavailability for meloxicam ranging between 72% and 100% F when administered to horses and ruminants (Calves: Coetzee et al ., ; Goats: Ingvast‐Larsson et al ., ; Horses: Toutain et al ., ; Sheep: Stock et al ., ; Camels: Wasfi et al ., ; Llamas: Kreuder et al ., ). Our study demonstrated oral F at 87% (range 39–350%).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies have demonstrated excellent bioavailability for meloxicam ranging between 72% and 100% F when administered to horses and ruminants (Calves: Coetzee et al ., ; Goats: Ingvast‐Larsson et al ., ; Horses: Toutain et al ., ; Sheep: Stock et al ., ; Camels: Wasfi et al ., ; Llamas: Kreuder et al ., ). Our study demonstrated oral F at 87% (range 39–350%).…”
Section: Discussionmentioning
confidence: 97%
“…Our study demonstrated oral F at 87% (range 39–350%). The lower range in F coincides with previous studies conducted in sheep (Stock et al ., ; 40%) and llamas (Kreuder et al ., ; 48%). As there are no other studies assessing bioavailability in sows, it is unclear whether variability in F should be expected in sows or other factors such as feeding regimen or drug formulation influenced this outcome.…”
Section: Discussionmentioning
confidence: 97%
“…Butorphanol and xylazine most likely provided some postoperative analgesia, but this would be short lived. Additional postoperative analgesia in our study was provided by administration of oral meloxicam, which has been shown to have good bioavailability in llamas …”
Section: Discussionmentioning
confidence: 99%
“…Plasma concentrations of MEL were determined using high-pressure liquid chromatography (Surveyor MS Pump and Autosampler; Thermo Scientific, San Jose, CA) with mass spectrometry detection (TSQ Quantum Discovery MAX; Thermo Scientific) as previously described (Kreuder et al, 2012). The accuracy of the assay for MEL in bovine plasma was 99 ± 3% of the actual concentration while the coefficient of variation was 5% determined on 4 sets of replicates for each of the following concentrations: 15, 150, and 1,500 ng/mL.…”
Section: Plasma Meloxicam Analysismentioning
confidence: 99%